How we got the Bible - Lightfoot, Neil R. (Baker Book House, 1963)
How accurate are modern translations such as the New International Version? Why does the Roman Catholic Bible have more books than most Protestant Bibles? How can we be sure that the Biblical message has been accurately preserved throught the centuries?